Ketogenic Diet as a weight loss diet- an over-hyped diet - Maisha, Marjana; Begum, Monirun; Yasmeen, B H Nazma (Northern International Medical College Journal, 2025)
Abstract not available Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 750-752